أثر تنمية الصادرات خارج المحروقات على النمو الإقتصادي في الجزائر 2000_2015 - بوديسة, أحمد; العبسي, علي; لبزة, هشام (جامعة الوادي - University of Eloued, 2020)
تعتبر عملية تنمية وتنويع الصادرات خارج المحروقات مصيرية للجزائر، لأنها تتيح لها فرصا لزيادة معدلات نموها وزيادة الطاقة الإنتاجية لمؤسستها وتوفير فرص العمل وتحقيق نمو اقتصادي، إذ أن زيادة الصادرات خارج المحروقات و تنميتها لم يعد أمرا اختياريا ولكنه أصبح شرطا جوهريا لضمان استقرار الإقتصاد الوطني، و هدف البحث إلى دراسة تأثير تنمية الصادرات خارج المحروقات على النمو الإقتصادي في الجزائر معبرا عنه بالناتج المحلي الإجمالي ورغم أن الصادرات خارج المحروقات خلال فترة الدراسة لم تتعدى %6 من الصادرات الإجمالية، إلا أن لها علاقة موجبة مع الناتج المحلي الإجمالي كما أن الجزائر مرغمة على تنمية الصادرات خارج المحروقات، قبل أن يتعرض اقتصادها لهزات عنيفة نتيجة أي اضطراب محتمل في أسواق المحروقات أو نتيجة التحرر الجمركي الكلي في تبادل السلع والخدمات بحيث تصبح الجزائر مفتوحة أمام المنتجات الأجنبية دون أن تكون قادرة على تحمل على اقتحام الأسواق الخارجية. The development and diversification of exports outside the fateful fuels Algeria, it allows them opportunities to increase their growth rates and increase production capacity for its enterprise and job creation, and economic growth, as exports outside the hydrocarbons and their is no longer optional but it has become essential to ensure the stability of the national economy, and objective research to study the effect of export development outside fuel On economic growth in Algeria expressed in GDP while exports out of fuel during the study period did not exceed 6% of total exports, but has a positive relationship with GDP as to Algeria to export out of fuel before its economy to fierce orgasms as a result of any potential disruption in oil markets or customs liberalization Total customs liberalization in the exchange of goods and services so that Algeria open to foreign products without being able to afford to break into foreign markets.
The impact of export development outside hydrocarbons on economic growth in Algeria 2000- 2015
مقال
Keywords: الصادرات خارج المحروقات، النمو الإقتصادي، الناتج المحلي الإجمالي; Non-hydrocarbon exports, economic growth, GDP